A Study on the Effect of Breakfast Habits on Blood Pressure and Academic Performance among University Students in Saudi Arabia - Bano, Rafia; Ahmad, Sana; Bahathig, Abeer A.; Fatima, Waseem (International Journal of Child Health and Nutrition, 2025)
Introduction: Skipping breakfast is becoming common and can significantly affect a person's physiological and psychological health. Objectives: To determine the prevalence and factors associated with skipping breakfast among undergraduate students of Saudi Arabia. Methods: A cross-sectional survey was conducted in two regions of Saudi Arabia using a self-designed and validated questionnaire that included demographic and anthropometric measurements with both open-ended and closed-ended questions. The sample size was 236 students, both adult males and females of age ≥ 18 years of age. Breakfast consumption was assessed using the single-question item: "How often do you eat breakfast?" (Almost every day, sometimes, rarely, or never). Skipping breakfast was defined as respondents indicating that they "sometimes," "rarely," or "never" have breakfast. Results: Out of a total sample of 236, only 108 participants (45.8%) were consuming breakfast, and 128 participants (54.2%) skipped breakfast in the morning. Cereals were consumed daily by only approximately 20% of the participants. Toast or bread, eggs, and tea/coffee were the most consumed breakfast by more than 50% of the subjects. The highest recognized reason for skipping breakfast is no time to eat in the morning. Age, Systolic Blood pressure, and BMI were found to be significantly associated with breakfast skipping. Conclusions: Evidence from observational studies suggests that skipping breakfast in real-world settings may contribute to weight gain and the development of overweight and obesity. Future research should explore other anthropometric measures beyond BMI and account for potential confounding factors.